Answers

The Brainliest Answer!
2015-02-02T18:34:48+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
If a and b are the roots of the quadratic equation x² - px + q = 0,

Sum of roots = a+b= -\frac{(-p)}{1}=p

Product of roots = ab= \frac{q}{1}=q

we need to find the value of a²+b².

(a+b)² = a² + b² + 2ab
⇒ p² = a² + b² + 2q
⇒  a² + b² = p² - 2q
2 5 2
2015-02-02T18:53:30+05:30
Here sum of the roots= -b/a
product of roots= c/a
Given b= -p
         a= 1
         c= q
sum of roots= -(-p)/1
                   = p
product of roots= q/1
                       = q
aa{2} +b{2} = (a+b){2} + 2ab
                        = p{2} + 2*q[/tex]
                        
1 5 1